Penerapan Metode Zachman Framework Terhadap Sistem Informasi Sumber Daya Manusia Kesehatan Di Dinas Kesehatan Kota Cirebon - Alamsyah, Samuel Sandy; Fibriani, Charitas (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The health worker information system is the interpretation of communicative data in graphical form. Basically this application is a technique for communicating the health human resource data to make information as a visual object. In this research, an analysis was carried out on the application of health worker information systems that aimed at optimizing the application. The optimal application is expected to facilitate the user in carrying out the achievement of the need for information. The results of the research and interviews are the implementation of Zachman Framework method obtains several perspectives or points of view about the application function. These perspectives or point of view will be useful in assisting the implementation of the progress on development design from that application